Islam Dayak: Dialektika Identitas Dayak Tidung dalam Relasi Sosial-Agama di Kalimantan Timur - Ahmad Muthohar; Anis Masykhur (STAI ALHIKMAH Jakarta, 2011)
Dayak Tidung is one of the communities of sub-Dayak from families of Murut who do dialectic and construct their own identities independently. Their civilized existence can be a driving force (trigger power) in building social integration that is often hurt by the conflict of ethnicity and religion. In addition, it could act as a breaker of the classical construction of Dayak identity attached to non-Muslims and non-Malays that could jeopardize the potency for social integration in East Kalimantan. This study is aimed to determine the dialectic of the identity of Dayak Tidung, especially in the aspect of social relation and religion. Thus this can be understood as: firstly the dialectic of religious identity and struggle of the identity of Dayak, secondly, the dynamics of the social-religious relation and its response in articulating Islam in the middle of the local identity of Dayak, and thirdly the dynamics of its religiousness and its relation to the community outside of itself. Keywords: relation, dialectics, identity Dayak Tidung adalah salah satu komunitas sub Dayak dari rumpun Murut yang melakukan dialektika dan mengkontruksi identitasnya secara mandiri. Keberadaannya yang civilized dapat menjadi kekuatan pendorong ( trigger power) dalam membangun integrasi sosial yang kerap terciderai konflik berbasis vis a vis etnisitas dan agama. Di samping itu bisa berperan sebagai pembongkar terhadap kontruksi klasik identitas Dayak yang lekat dengan non Muslim dan non Melayu yang dapat membahayakan potensi integrasi sosial di Kalimantan Timur. Penelitian ini dimaksudkan untuk mengetahui dialektika identitas Dayak Tidung, terutama dalam aspek relasi sosial dan Agama. Dengan demikian bisa dimengerti beberapa hal. Pertama, dialektika keberagamaan dan pergulatan identitas ke Dayakannya. Kedua, dinamika Relasi Sosial-Agama dan responsinya dalam mengartkulasikan agama (Islam) ditengah identitas lokal Dayak. Ketiga, dinamika keberagamaannya dan relasinya terhadap komunitas di luar dirinya. Kata Kunci: relasi, dialektika